FAKTOR-FAKTOR YANG MEMPENGARUHI KEIKUTSERTAAN PROGRAM PIL KB PADA PUS DI WILAYAH KERJA PUSKESMAS MABELOPURA PALU TAHUN 2012 - Diky Hardiyansyah; Nita Damayanti (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram)
The choice of contraceptive method is an effort made by a woman to look for contraceptive methods that are suitable for her condition, this is because the contraceptive choice menu is influenced by the variety of methods available. This study aims to determine the factors that influence EFA participation in family planning programs. Data retrieval is done by interview techniques, using a case control design and carried out in the work area of ??Mabelopura Health Center with a total sample of 96 people. The population of the study was EFA participants in the pill and injection KB in the Pusekesmas Mabelopura working area that met the criteria. The results showed that the influence of demographic factors (age, religion) had a non-significant P value (P> 0.05), for socio-economic factors (education level, income) had a non-significant P value (P> 0.05) , the factor of the number of children has a P value that is not significant (P> 0.05), the disease history factor has a P value that is not meaningful, the influence factor of others has a meaningless P value, and the influence factor of mass media (newspapers, TV, and radio) also has a meaningless P value (> 0.05).